The family medicine accelerated track at Texas Tech University Health Sciences Center: results from a 10-year program to bend the primary care curve - Betsy Goebel Jones; Ronald C. Cook; Felix Morales; Keeley Hobart; Steven L. Berk (Medical Education Online)
Background Texas is one of the states with the lowest access to usual sources of primary care; most critically, family medicine (FM) has been projected to have the greatest physician shortage increase between 2018 and 2032. Texas Tech University Health Sciences Center (TTUHSC) School of Medicine developed the Family Medicine Accelerated Track (FMAT), a 3-year curriculum that culminates in the MD degree and links medical students to FM residency programs at TTUHSC campuses in Lubbock, Amarillo or the Permian Basin. This article reflects on 10 years of experience with the program, and particularly its impact on the primary care physician workforce in Texas.Curriculum Design TTUHSC medical students in the traditional curriculum complete the Phase 1 pre-clinical curriculum in Lubbock and are distributed for Phases 2 and 3 (MS3/MS4 years) among campuses in Lubbock, Amarillo and the Permian Basin. Similarly, FMAT students complete Phase 1 in Lubbock. For Phase 2 clinical clerkships, their curriculum is delivered on the campus (which may include Lubbock) where they will typically complete 3 years of FM residency training.Program Outcomes In the 2 years prior to the graduation of the first FMAT class, just over 11% of the graduating class matched into FM. In the decade since, the numbers have varied from year to year (often as high as 17–19% of the class matching into FM) but have always exceeded the pre-FMAT numbers. For the classes 2013 through 2023, 115 students began FMAT training; 90 of them (78%) graduated in 3 years with the MD degree and began FM residency training. Of those 90, 56 have now graduated from residency and taken positions in the primary care physician workforce. Of that group, 86% are practicing in Texas, 64% are in West Texas, and 69% are in rural or underserved communities.